Aloe vera and artemisia vulgaris hydrogels: exploring the toxic effects of structural transformation of the biocompatible materials. (2nd November 2021) - Frasat, Taskeen; Tulain, Ume Ruqia; Erum, Alia; Saleem, Uzma; Sohail, Muhammad Farhan; Kausar, Rizwana
Abstract: Objectives: This study was aimed to evaluate the toxicity profile of hydrogels of plant-derived mucilage from Aloe vera and Artemisia vulgaris used for various drug delivery applications, yet no such toxicity study has been reported for the toxicity evaluation of 3 D structures. New Drug carriers should be harmless for drug delivery applications. Methods: Acute and sub-acute (repeated dose) oral toxicity studies were conducted following OECD 407 and 425 guidelines. In vitro toxicity through hemolysis and MTT assay were checked against RBC's and human macrophages respectively. Results: The hemolysis and MTT assay showed good compatibility of hydrogels with blood components. Mutagenicity testing showed no genotoxic effects of hydrogels. In vivo toxicity evaluation was done in female albino rats and rabbits. General behavior, adverse effects, clinical signs and symptoms, and mortality were recorded for 14 days post-treatment which showed no significant ( p < 005 ) abnormality. Hematological and biochemical parameters including LFTs and RFTs appeared to be normal with slight variations in the treated groups. The normal architecture of kidney, liver, heart and intestine was evident upon histopathological analyses. Conclusion: Hence, the results suggested that the 3 D structure of Aloe vera and Artemisia vulgaris based hydrogels are safe upon ingestion and can be used for drug delivery science being cheap, natural and biocompatible.